2022
DOI: 10.1186/s13584-022-00537-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the primary care pediatrician's role in managing psychosocial issues: a cross sectional study of pediatricians and parents in Israel

Abstract: Background Psychosocial issues are an integral part of children's health and well-being, and it is widely acknowledged that pediatricians should be involved in their management. We examined the current perception of the pediatrician’s role in the management of psychosocial problems in Israel from the perspective of parents and pediatricians, and identified possible barriers. Methods We assessed parents' and pediatricians' perspectives through a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The survey results indicate that pediatricians have limited knowledge on a variety of developmental, behavioral and emotional issues. These findings complement those found in a previous study in Israel about pediatricians’ roles in management of psychosocial issues [ 9 ], and are supported by the qualitative results. Additionally, the qualitative results show that some pediatricians in the community adopt a more complex role, but the system (including training programs and HMOs) has not adapted nor supported this change.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The survey results indicate that pediatricians have limited knowledge on a variety of developmental, behavioral and emotional issues. These findings complement those found in a previous study in Israel about pediatricians’ roles in management of psychosocial issues [ 9 ], and are supported by the qualitative results. Additionally, the qualitative results show that some pediatricians in the community adopt a more complex role, but the system (including training programs and HMOs) has not adapted nor supported this change.…”
Section: Discussionsupporting
confidence: 90%
“…The appropriate tools, skills and exposure required for community pediatric work [ 5 , 8 ] are inadequately provided. An Israeli study regarding the management of psychosocial issues found that many pediatricians who work in the community face psychosocial issues in their practice, without having the training, time or confidence to provide the support and treatment needed [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. Sun et al, 2018; Voigt, 2022). In Israel, community pediatricians are responsible for referrals to specialist diagnostic teams, yet they have little involvement in detecting developmental-behavioral conditions (Nissanholtz-Gannot et al, 2021) and discussions of psychosocial issues are largely initiated by parents (Gadassi et al, 2022). Parents likely require assistance in adequately identifying and communicating their concerns to primary care doctors who can, in turn, benefit from potential areas of concern being highlighted to them in an efficient manner.…”
Section: Discussionmentioning
confidence: 99%